Economic Spillovers, Structural Reforms and Policy Coordination in the Euro Area - Aarle, Bas van.; Aarle, Bas van.; Weyerstrass, Klaus.; Weyerstrass, Klaus. (Contributions to Economics,, 2008)
This book analyses economic interdependence in the Euro Area and provides estimates of the sign and size of economic spillovers and the impact of economic policy coordination concerning structural and budgetary policies on economic performance in the Euro Area. In the different chapters of the book, the following topics are studied: (i) the link between fiscal and monetary policies in the Euro Area; (ii) the link between public debt and long-term interest rates in the Euro Area; (iii) the link between budgetary stabilisation and the level of public debt in the Euro Area; (iv) the spillovers from structural reforms in the Euro Area, (v) the scope for the coordination of fiscal policies and of structural reforms in the Euro Area, and (vi) wage flexibility in the Euro Area.